Anti‐LGI1, anti‐GABABR, and Anti‐CASPR2 encephalitides in Asia: A systematic review - Ghimire, Prinska (Brain Behav, 2020)
AIM: We aim to review the literature to collate and describe features of encephalitides arising from autoantibodies against leucine‐rich glioma‐inactivated 1 (LGI1), gamma aminobutyric acid receptor (GABABR), and contactin‐associated protein‐like 2 (CASPR2) in Asian populations and compare them with findings of Western studies. METHODS: Peer‐reviewed articles published till 24 May 2020 were searched, and original, full‐text studies from Asia with serum/CSF antibody‐based diagnosis and at least 2 patients were selected. Twenty‐four studies with 263 patients (139 anti‐LGI1, 114 anti‐GAGABR, and 10 anti‐CASPR2) were included. Data were pooled to produce descriptive information on demographics, clinical characteristics, diagnostics, treatments, and outcome. RESULTS: The mean age was 54.2 (anti‐LGI1), 55.2 (anti‐GABABR), and 47.7 years (anti‐CASPR2), with an overall male predominance of 62.0%. Commonest clinical features across all types were seizures (87.5%), memory deficits (80.7%), psychiatric disturbances (75.9%), and altered consciousness (52.9%). Four anti‐LGI1, 40 anti‐GABABR, and 1 anti‐CASPR2 patients had tumors. CSF, MRI, and EEG were abnormal in 33.3%, 54.1%, and 75% patients in anti‐LGI1; 60.0%, 49.6%, and 85.7% in anti‐GABABR; and 50%, 44.4%, and 100% in anti‐CASPR2 patients, respectively. 95.6% patients received first‐line therapy alone (steroids/IVIG/Plasma therapy), and 4.4% received second‐line therapy (rituximab/cyclophosphamide). 91.7%, 63.6%, and 70% of patients had favorable outcomes (modified Rankin Score 0–2) with mortality rates at 2.5%, 23.2%, and 0% in the three types, respectively. CONCLUSION: Our findings suggest that these disorders present in Asian patients at a relatively young age often with features of seizures, memory deficits, and psychiatric disturbances and usually demonstrate a favorable clinical outcome.